ANALISIS PERMASALAHAN ANAK AUTIS SPECTRUM DISORDER (ASD) DI RUMOH TERAPI TABINA BANDA ACEH - Dhia Rahmadika Dhia; Syahnaz Saqila Syahnaz; Shiva Haura Shiva (Nunchi : Islamic Parenting Journal, 2024)
Autism Spectrum Disorder (ASD) is a comprehensive developmental disorder that results in barriers in socialization, communication and behavior. The purpose of this study was to determine the problems experienced by children with Autism Spectrum Disorder (ASD) at Rumoh Terapi Tabina Banda Aceh. This research uses descriptive qualitative method. Qualitative research is the methodological approach used in this study. Descriptive data from observable people and actors in the form of written or oral statements are used in qualitative research procedures. The data collection techniques used were observation, interview and documentation. The results showed that 7-year-old H has ASD disorder since he was 3 years old H has been delivered to Rumoh Terapi Tabina with verbal communication disorder that is not smooth, unstable behavior and cognitive impairment.